Principles of macroeconomics - Stiglitz, Joseph E. (W.W. Norton & Company, 1997)
A distinctive three-part core for the macroeconomic presentation, emphasizing microfoundations and economic growth. Growth and long-run issues receive early emphasis, with international topics prominent throughout the discussion. Students work within the aggregate supply and demand framework throughout.